2018
DOI: 10.31730/osf.io/jtkn2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Colonialism and narratives of human origins in Asia and Africa

Abstract: In their seminal works on postcolonialism, Edward Saïd (in Orientalism) and V.Y. Mudimbe (in The Idea of Africa) proposed that Asia and Africa, respectively, were constructs created around the notion of their otherness. Both regions were viewed as infantile, primitive, and homogenous entities that fell outside the domain of civilized (i.e. Western) humanity. These constructs shaped scientific perceptions of both continents over the course of several centuries and have continued to be operative over the last 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Several researchers are working to right these historical wrongs, addressing the scientific racism underpinning interpretations of human culture (e.g. Athreya & Rogers Ackermann 2019;Porr & Matthews 2019;Read 2006), while others are re-evaluating the idea that wooden spears are a 'simple' technology (e.g. Garofoli 2015;Haidle 2009).…”
Section: Historicising and Contextualising References To Ethnographicmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers are working to right these historical wrongs, addressing the scientific racism underpinning interpretations of human culture (e.g. Athreya & Rogers Ackermann 2019;Porr & Matthews 2019;Read 2006), while others are re-evaluating the idea that wooden spears are a 'simple' technology (e.g. Garofoli 2015;Haidle 2009).…”
Section: Historicising and Contextualising References To Ethnographicmentioning
confidence: 99%
“…One solution, proposed by scholars working to decolonise human origins, is to desist from representing early humans as primitive. By reframing in this way, the use of ethnographic analogy to more accurately represent necessary skills and abilities in use of technologies becomes less problematic (Athreya & Rogers Ackermann 2019). It is also important to avoid ' cherry-picking' ethnographic examples to support a given model (French 2019).…”
Section: Contextualising Pleistocene Hunting Technologiesmentioning
confidence: 99%
“…Recent work in aDNA, archeology and fossil discoveries reveal that second model is incorrect in the sense of Pleistocene Homo having genomic "regional continuity" with contemporary populations and that first model is overly simplistic. 3,50 Twenty years ago, Alan Templeton offered an alternative to these two positions, and since then others have also emerged. Templeton proposed the "lattice" model, 112 where he pointed out that patterned exchange of genetic materials appears to have been sporadically present across populations of the genus Homo throughout the Pleistocene, rendering both models insufficient and misleading.…”
Section: Box 1 Examples Of Niche Construction In the Pleistocenementioning
confidence: 99%
“…For example, it has been recently demonstrated that primatological fieldwork is focused on a few particular taxa from a small number of field sites, biasing the broader perspective of what primates do 1,2 . Similarly, there is a bias in paleoanthropology that privileges Western voices and the hypothetico‐deductive model of knowledge construction 3 . As others have shown there is a bias in where we dig, what we publish, and how we talk and think about human evolution 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation